Long-term hydrological alterations and the agricultural landscapes in the Mekong Delta: insights from remote sensing and national statistics - Hui, Tay Ru (2022)
The Vietnamese Mekong Delta (VMD) is one of the most important food baskets in Southeast Asia, contributing to more than half of the country's food production capacity and the majority of its rice exports. Constantly threatened by a multitude of environmental pressures, including climate change-induced sea-level rise, delta-wide land subsidence, sedimentation reduction and, more recently, riverbed mining, steps towards the sustainable development of the VMD is becoming increasingly vulnerable. In this paper, we examine the effect of hydrological alterations of agricultural landscape in the VMD, more specifically, the temporal trends of triple rice crop in the Long Xuyen Quadrangle (LXQ). Landsat satellite data was used to map active rice paddy sites across the three major rice cropping seasons and identify the temporal distribution of triple rice crop areas over the last 24 years (1995–2019). Results were interpreted alongside official statistical data on agriculture from Vietnam and corroborated with ground truth data points from the study site. Our results reveal a notable fall in Landsat-detected triple rice crop area between 2016 and 2019, corroborating with both literature and agricultural data indicating an increase in aquaculture areas. Here, we take note for the first time the underlying links between riverbed mining and agricultural shifts in the VMD, which could highlight important policy and management implications for the local government in order to ensure environmental sustainability and food security. We argue that a tighter and more effective regulation of riverbed mining practices in the region is both integral and necessary for the agricultural sustainability of the VMD.